In vitro Screening and Optimization of IAA Production from Plant Growth Promoting Rhizobacteria Burkholderia cepacia UPMB3 (Plant Tissue Culture and Biotechnology, 2018)
Burkholderia cepacia UPMB3 is an important plant growth promoting rhizobacteria isolated from oil palm rhizosphere which is considered to promote plant growth directly or indirectly. The IAA was extracted, purified, detected and confirmed by thin layer chromatography analyses f r om t h e strain UPMB3 of B. cepacia. Rf value was compared with the authentic IAA. Maximum 50 μg/ml IAA was produced in the medium supplemented with 4 mg/ml L-tryptophan, under shaken conditions at 150 rpm in seven days incubation at pH 7. The bacterial extract significantly influenced the growth of oil palm seedlings producing shoot, root, leaf and leaf length compared to control.Plant Tissue Cult. & Biotech. 28(1): 25-34, 2018 (June)